Tingkat Kebugaran Jasmani Peserta Didik SMP Negeri 2 Airmadidi Tahun Ajaran 2024/2025 - Dea Amarilis Sapii; Yuliana Sattu; Jes. J Mangindaan (STIKES Columbia Asia Medan, 2024)
Moving on from the reality found in the field, based on the results of preliminary observations in the SMP Negeri 2 Airmadidi school environment, some students do not master and have good physical condition components. The level of physical fitness of the students is not yet known. Therefore, it is necessary to conduct an internal survey through the implementation of tests and measurements carried out correctly and thoroughly. Lack of attention and coaching to the physical fitness level of students. Students have not shown a good level of physical fitness, these symptoms are shown when teaching and learning activities take place students quickly experience fatigue, lack of concentration, lack of passion and enthusiasm and motivation in participating in the teaching and learning process. The research method used in this research is descriptive quantitative. The final results in the form of physical fitness categories are obtained based on a combination of 5 (five) test items as listed in Table 4.13, where it can be seen that most of the physical fitness of male students is in the Moderate category or around 87.50% while the physical fitness of female students is in the less category or around 95%.